Applying Gaia and AUML for the development of multiagent‐based control software for flexible manufacturing systems: addressing methodological and implementation issues. (21st January 2015) - Duran‐Faundez, Cristian; Ramos, Mario; Rodriguez, Pedro
Summary In this article, we present the development of a simple multiagent‐based system for the control of a flexible manufacturing system. We followed the stages of a methodology specially conceived for the development of agent‐based system, which is an integration of the classical methodology for agent‐oriented analysis and design Gaia, and AUML (Agent‐Unified Modeling Language). We adopted as study case the CIMUBB Laboratory at the University of Bio‐Bio, which has a flexible manufacturing system including three flexible manufacturing cells interconnected by a conveyor belt. In the analysis stage, we identified roles involved, and we design models representing roles and protocols. In the design stage, we applied Gaia agent, services, and acquaintance models from Gaia, and we complemented with AUML as the adopted methodology suggests. With the developed models, we constructed a fully functional system where each agent was built as an independent process tree. Agents communicate by passing messages through the Ethernet network with socket interfaces. Various tests executed in our laboratory scale manufacturing system show the effectiveness of our implementation. Copyright © 2015 John Wiley & Sons, Ltd.